2015
DOI: 10.1007/s10529-015-1894-1
|View full text |Cite
|
Sign up to set email alerts
|

One step bioconversion of waste precious metals into Serratia biofilm-immobilized catalyst for Cr(VI) reduction

Abstract: A 'one pot' conversion of precious metal waste into new catalyst for waste decontamination was shown in a continuous flow system based on the use of Serratia biofilm to manufacture and support catalytic Pd-nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Using Serratia sp. biofilms, developed on the polyurethane foam, palladium was recovered as biofilm-Pd 0 nanocatalyst from industrial wastes [65]. The biorecovery of Pd(II) occurs in three concomitant steps: (i) biosorption with biomass via interactions with surface functional groups viz.…”
Section: Au + 8cn + O + 2h O → 4au Cn + 4ohmentioning
confidence: 99%
“…Using Serratia sp. biofilms, developed on the polyurethane foam, palladium was recovered as biofilm-Pd 0 nanocatalyst from industrial wastes [65]. The biorecovery of Pd(II) occurs in three concomitant steps: (i) biosorption with biomass via interactions with surface functional groups viz.…”
Section: Au + 8cn + O + 2h O → 4au Cn + 4ohmentioning
confidence: 99%
“…Macaskie, unpublished work), but the same study showed that catalyst stability was retained completely by bio-Pd of E. coli, and also by the related Serratia sp. by self immobilisation of the bacteria as a biofilm onto a support [81]. The adhesive and cohesive strength were quantified via a micromanipulation method [81] and examination of a flow-through column system by MRI showed no evidence of catalyst loss under load [20].…”
Section: Comparison Of Bio-pd Ecoli With Bio-pd Ddesulfuricansmentioning
confidence: 99%
“…These include commercially relevant synthetic chemistry, (Deplanche et al ., ), sometimes with better product selectivity in comparison with established catalysts (Zhu, ). Bacterially supported catalyst is recoverable in repeated reaction cycles without attrition or loss (Bennett et al ., ), and hence, this approach is beneficial in terms of catalyst conservation and reduced wastage, especially where the catalyst is self‐immobilized onto a tightly adhering biofilm for application in a continuous process (Yong et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…This approach pioneers a new area of environmental nanotechnology where the potential hazards of nanoparticle migration (Lead and Valsami‐Jones, ; Valsami‐Jones and Lynch, ) are forestalled by the retention of the catalytic NPs onto the micron‐sized, robust ‘carrier’ bacterial cells and macroscopic biofilm, where the catalyst ensemble remains tightly bound (Yong et al ., ).…”
Section: Introductionmentioning
confidence: 97%